2016
DOI: 10.1128/aem.02651-15
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Ecology of Viruses in Hyperarid Desert Soils

Abstract: In recent years, remarkable progress has been made in the field of virus environmental ecology. In marine ecosystems, for example, viruses are now thought to play pivotal roles in the biogeochemical cycling of nutrients and to be mediators of microbial evolution through horizontal gene transfer. The diversity and ecology of viruses in soils are poorly understood, but evidence supports the view that the diversity and ecology of viruses in soils differ substantially from those in aquatic systems. Desert biomes c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 80 publications
3
84
2
Order By: Relevance
“…The rapidly growing database of viral environmental sequences has revealed that most sequences (approximately 90%) do not have homologs in public databases, and are typically labeled as viral dark matter38. The same phenomenon occurred that an average of 2/3 of the genes within dsDNA viruses cannot be assigned a biological function or taxonomic affiliation according to a Basic Local Alignment Search Tool homology19. This may be one of the reasons why viral species distribution is similar among viromes from different environmental samples.…”
Section: Discussionmentioning
confidence: 99%
“…The rapidly growing database of viral environmental sequences has revealed that most sequences (approximately 90%) do not have homologs in public databases, and are typically labeled as viral dark matter38. The same phenomenon occurred that an average of 2/3 of the genes within dsDNA viruses cannot be assigned a biological function or taxonomic affiliation according to a Basic Local Alignment Search Tool homology19. This may be one of the reasons why viral species distribution is similar among viromes from different environmental samples.…”
Section: Discussionmentioning
confidence: 99%
“…Lower temperatures are more suitable for bacterial and viral survival. The ultraviolet radiation from the sun inactivates viruses on the surface of the soil, but viruses in deeper soil strata are protected from this (Rodríguez-L azaro et al, 2012;Zablocki et al, 2016). In loamy soil samples, at pH 7.5, poliovirus and echovirus were recovered after 110e130 days at 3e10 C compared to recovery 40e90 days at 18e23 C (Bagdasaryan, 1964).…”
Section: Effect Of Soil Properties and Environmental Variables On Thementioning
confidence: 99%
“…However, the diversity and ecological functions of viruses in these arid ecosystems are mostly unknown (2). Virus research in arid soils has primarily focused on the taxonomic composition associated with surface soils and soil-lithic interfaces (310) and has revealed a wide diversity of virus taxa, mostly composed of tailed phage families (order: Caudovirales ).…”
Section: Genome Announcementmentioning
confidence: 99%